CONTROL AND SUSTAINABILITY OF THE REGIONAL (NATIONAL) INTEGRATED RADIO NAVIGATION SYSTEM. - Baranov, G. L.; Koshevoy, A. A.; Skorik, E. T. (Problems of Informatization and Management, 2021)
System concepts of controllability and stability of navigation definitions are introduced for information fields of pulse-phase radio navigation systems (IFRNS) of regional (national) base, integrated with global satellite radio navigation systems such as GNSS. The conditions of functioning and the composition of technical means are determined to ensure the controllability and stability of positioning and navigation, the maintenance of which is provided by national means within the regional boundaries of the zone of use of the system by civil and special users. The concept of stability of the system in the presence of interference and other external influences is clarified.